A 2020 Update on 20/20 X 2: Diplopia after Ocular Surgery. Issue 4 (2nd October 2021) - Klein, Shelley
ABSTRACT: There is nothing more disheartening for our patients to go through successful ocular surgery only to experience unexpected post-operative diplopia. Diplopia following any type of ocular or periocular surgery is a known risk. Despite advances in surgical techniques, the strabismus team continues to get referrals for this unwanted result. This symposium will address the incidence, mechanism and treatment of post-operative diplopia following various types of ocular surgery such as retinal, orbital, glaucoma, iatrogenic monovision and more. Both surgical and non-surgical treatments will be presented to give attendees a better understanding of how to help their patients. Additionally, and perhaps more importantly, ways of recognizing signs that could forewarn of post ocular surgery diplopia will be discussed.